The Mass-size Relation from Clouds to Cores. II. Solar Neighborhood Clouds - Kauffmann, J; Pillai, T; Shetty, R; Myers, P. C; Goodman, A. A (The Astrophysical journal, 2010)
We measure the mass and size of cloud fragments in several molecular clouds continuously over a wide range of spatial scales (0.05 {approx}< r/pc {approx}< 3). Based on the recently developed 'dendrogram-technique', this characterizes dense cores as well as the enveloping clouds. 'Larson's Third Law' of constant column density, m(r) {proportional_to} r {sup 2}, is not well suited to describe the derived mass-size data. Solar neighborhood clouds not forming massive stars ({approx}<10 M {sub sun}; Pipe Nebula, Taurus, Perseus, and Ophiuchus) obey m(r) {<=} 870 M {sub sun}(r/pc){sup 1.33}. In contrast to this, clouds forming massive stars (Orion A, G10.15 - 0.34, G11.11 - 0.12) do exceed the aforementioned relation. Thus, this limiting mass-size relation may approximate a threshold for the formation of massive stars. Across all clouds, cluster-forming cloud fragments are found to be-at given radius-more massive than fragments devoid of clusters. The cluster-bearing fragments are found to roughly obey a mass-size law m {proportional_to} r {sup 1.27} (where the exponent is highly uncertain in any given cloud, but is certainly smaller than 1.5).